The metaphysics of historical Jesus research: a prolegomenon to a future quest for the historical Jesus - Rowlands, Jonathan (Routledge, Taylor & Francis Group, 2023)
Part I: Worldview and Historiographical Decision-Making; 1. Theology and History, Then and Now; 2. Defining Metaphysics; 3. The Concept of a Worldview; 4. Worldviews and Historiography; 5. Characterising Secular Scholarship; Part II: Worldviews and Historical Jesus Research; 6. Metaphysics and the First Quest; 7. Metaphysics and the Second Quest; 8. Metaphysics and the Third Quest; 9. Metaphysics and N. T. Wright; 10. Expanding the Boundaries of Historical Jesus Research.